2014
DOI: 10.1108/jsm-09-2012-0171
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate social responsibility (CSR) performance and perceived brand quality on customer-based brand preference

Abstract: Purpose – This paper aims to investigate how corporate social responsibility (CSR) performance (i.e. to the environment, society and stakeholders) and perceived brand quality influence brand preference. The mediating effect of perceived brand quality on the relationship between CSR performance and brand preference is also studied. Design/methodology/approach – In 2011, 243 valid responses to questionnaire surveys were collected from a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(76 citation statements)
references
References 79 publications
2
61
1
Order By: Relevance
“…Within hotels in North America, the findings reveal that companies who believe they incorporate green marketing into their business/strategy perceive greater guest visits per year, longer guest visits, greater guest satisfaction, higher revenue, greater profits, and higher daily rates. Indeed, these findings positively support a number of authors who declare that that socially and environmentally responsible actions do in fact result in increased customer satisfaction and brand value [3,[19][20][21]. Overall, as public concern for the environment increases, it is of the utmost importance that corporations integrate environmental concerns into their marketing, management strategies, and development of their products and services [42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Conclusion and Future Researchmentioning
confidence: 52%
See 1 more Smart Citation
“…Within hotels in North America, the findings reveal that companies who believe they incorporate green marketing into their business/strategy perceive greater guest visits per year, longer guest visits, greater guest satisfaction, higher revenue, greater profits, and higher daily rates. Indeed, these findings positively support a number of authors who declare that that socially and environmentally responsible actions do in fact result in increased customer satisfaction and brand value [3,[19][20][21]. Overall, as public concern for the environment increases, it is of the utmost importance that corporations integrate environmental concerns into their marketing, management strategies, and development of their products and services [42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Conclusion and Future Researchmentioning
confidence: 52%
“…A prominent trend across studies is that socially and environmentally responsible actions do in fact result in increased customer satisfaction and brand value [3,[19][20][21]. One term that is consistently used throughout the literature is 'corporate social responsibility' (CSR); this can be interpreted as a company's contribution to sustainable development.…”
Section: Communicating Corporate Sustainabilitymentioning
confidence: 99%
“…Previously presented studies primarily recognised the importance of CSR in large manufacturing enterprises and within the hotel (lodging) sector. To date, research findings into CSR in hotel industry have confirmed that if hotel organizations adopt and integrate CSR into their organizational strategies, they can facilitate innovativeness (Čivre and Gomezelj Omerzel 2015;Calveras 2015); increase and/or improve their organizational competitiveness (Kang et al 2015;Garay and Font 2012) and brand image (Tingchi et al 2014); boost employees' and customers' loyalty (García de Leaniz and Rodríguez Del Bosque Rodríguez 2015; Lee 2016); conserve environments (Rahman and Post, 2012), while at the same time contributing to solving problems in society that may arise (Smith and Ong 2015). According to Chen (2015) travellers are progressively more concerned with how tourist companies make their money and are expecting businesses to engage in responsible activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the literature review (De Grosbois, D. 2012;DiPietro et al 2013;Dutta et al 2008;EU Commission 2016;Fernandez-Feijoo et al 2014;Golob and Bartlett 2007;GRI 2016;Hsieh 2012;Hu et al 2010;Jamali 2008;Jones et al 2016;Perramon et al 2014;Rahman and Post 2012;Blackburn 2007, Sanchez-Gutierrez et al 2011;Scanlon 2007;Tingchi et al 2014), 28 CSR indicators belonging to four major CSR dimensions (local community, environment, marketplace policy, and human resources) were identified. Special attention was paid to indicators included in the GRI's -G4 sustainability reporting guidelines (46 general guiding aspects of CSR included in three categorieseconomic, environmental, and social) and the EU Awareness raising questionnaire for CSR (26 generic questions included in four CSR dimensions -local community, environment, marketplace policy, and human resources) (EU Commission 2016; GRI 2016).…”
Section: Instrument Designmentioning
confidence: 99%
“…The more customers identify with the brand, the more likely they are to feel satisfied (Bhattacharya & Sen, 2003). Customers' brand preference can be enhanced by CSR performance (Liu, Wong, Shi, Chu, & Brock, 2014). Meanwhile, companies can influence customer satisfaction in various ways by meeting their CSR (Luo & Bhattacharya, 2006).…”
Section: Consumer Awareness Of Csr and Its Influence On Brand Satisfamentioning
confidence: 99%